Modern Quantum Mechanics - Sakurai, J. J.; Napolitano, Jim J. (New Delhi: Pearson India, 2014)
Modern Quantum Mechanics is a comprehensive book for undergraduate students of Quantum Mechanics. The book comprises chapters on quantum dynamics, theory of angular momentum, symmetry in quantum mechanics, approximation methods, scattering theory, identical particles, and relativistic quantum mechanics. In addition, the book consists of several examples and chapterwise questions for thorough revision and final practice. This book is essential for students preparing for NET and GATE.
Appendix A-B 499-512p.; Bibliography 513-514p.; Index 515-520p.